Uji Patogenisitas Zoospora Kapang Lagenidium giganteum terhadap Larva Instar-2 Nyamuk Aedes aegypti Skala Laboratorium (PATHOGENICITY TEST OF ZOOSPORA LAGENIDIUM GIGANTEUM FUNGI AGAINST AEDES AEGYPTI LARVAE 2nd UNDER LABORATORY CONDITION) - Indrawati, Agustin; Sudarwanto, Mirnawati; Tampubolon, Mangaraja Pidoli; Soejoedono, Retno Damayanti; Wibawan, I Wayan Teguh (Jurnal Veteriner, 2012)
Dengue Haemorrhagic fever (DHF) is one of fearsome diseases in society. Incidence of the disease isincreasing. Dengue fever is caused by dengue virus and transmitted by Aedes aegypti mosquito vector.Various chemical controls have been conducted to prevent the spread of the disease, but active contents ofthe chemical controlling substances are suspected causing many negative effect, in environment, such asvector resistance, death of non target living creatures, and environmental contamination.This researchobjective was to find an alternative solution in order to control the dengue vector by using entomopathogenicfungi as biological control agent. This research was conducted by isolation and identification of fungiinfecting mosquito larvae. Macroscopic observation revealed that one of the nine isolation products wasLagenidium giganteum. The effectiveness test in laboratory showed the zoospore LD50 to Ae.aegypti larvaeof instar 2nd was 2,35 x 106 zoospore/ml, while the LD95 value was 1,35 x 107 zoospore/ml. The oosporeeffectiveness test showed LD50 was 6,7 x 102 oospore/ml and LD95 was 1,94 x 103 oospore/ml. Using LPCBdye and blue tolouidin 2,5%, the infection mechanism of L.giganteum fungi in Ae.aegypti mosquito larvawas detected. The research is concluded that the entomophatogen fungi L. giganteum was very prospectiveto be used as a biological control agent against vector of DHF.
Keywords: Dengue Haemorrhagic fever (DHF), Aedes aegypti, Lagenidium giganteum